2015
DOI: 10.1177/0363546515597489
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Attenuates 30-kDa Fibronectin Fragment–Induced Chemokine and Matrix Metalloproteinase Expression by Meniscocytes and Articular Chondrocytes

Abstract: These observations provide support for the use and further trials of PRP in management of cartilage and meniscal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…We considered that the superior healing process and chondroprotective phenomenon that occurred in the PRF-augmented suture group were attributable not only to the anabolic cytokines but also the presence of a number of anti-inflammatory mediators that can potentially affect numerous overlapping pathways simultaneously [ 46 ]. For instance, PRP was found effective in attenuating the effects of fibronectin fragments on both chondrocyte and meniscocytes production of procatabolic chemokines and matrix metalloproteinases [ 47 ]. In the future, the role of PRF in modulating inflammatory mediators warrants further in vitro and in vivo studies using large animals to further confirm the potential of clinical translation while exploring the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that the superior healing process and chondroprotective phenomenon that occurred in the PRF-augmented suture group were attributable not only to the anabolic cytokines but also the presence of a number of anti-inflammatory mediators that can potentially affect numerous overlapping pathways simultaneously [ 46 ]. For instance, PRP was found effective in attenuating the effects of fibronectin fragments on both chondrocyte and meniscocytes production of procatabolic chemokines and matrix metalloproteinases [ 47 ]. In the future, the role of PRF in modulating inflammatory mediators warrants further in vitro and in vivo studies using large animals to further confirm the potential of clinical translation while exploring the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, wound healing, and regeneration PRP has been shown to attenuate fibronectin-induced expression of several pro-inflammatory chemokines and MMPs in human meniscocytes and articular chondrocytes, thus supporting use of PRP in the management of cartilage and meniscal injuries [64]. It was also proposed as a potential treatment for endometritis in cattle based on its abilities to downregulate the expression of pro-inflammatory genes in primary cultures of bovine endometrial cells after 48 h of incubation [65], and decreased intrauterine inflammatory response in mares [66].…”
Section: Prp Stimulates Endometrial Cell Proliferation and Migrationmentioning
confidence: 93%
“…PRP represents a safe and cheaper alternative to recombinant growth factors, releasing an autologous and appropriate cocktail of growth factors within a natural and physiological range at the site of injection. In vitro, it has been shown that PRP has a proliferative effect on autologous chondrocytes and mesenchymal stem cells [53,54] and attenuates their pro-inflammatory chemokine and metalloproteinase expression [55]. Clinical studies evaluating the efficacy of PRP, prepared with Regen Lab technology, for the treatment of knee osteoarthritis demonstrated significant effects on pain relief and functional improvement, especially for those patients with lower degrees of OA, with safety of use and no serious adverse events attributable to the treatment [8,[56][57][58][59][60][61][62].…”
Section: Platelet Rich Plasma In the Treatment Of Osteoarthritismentioning
confidence: 99%